2021
DOI: 10.3390/biom11030408
|View full text |Cite
|
Sign up to set email alerts
|

TRIM32: A Multifunctional Protein Involved in Muscle Homeostasis, Glucose Metabolism, and Tumorigenesis

Abstract: Human tripartite motif family of proteins 32 (TRIM32) is a ubiquitous multifunctional protein that has demonstrated roles in differentiation, muscle physiology and regeneration, and tumor suppression. Mutations in TRIM32 result in two clinically diverse diseases. A mutation in the B-box domain gives rise to Bardet–Biedl syndrome (BBS), a disease whose clinical presentation shares no muscle pathology, while mutations in the NHL (NCL-1, HT2A, LIN-41) repeats of TRIM32 causes limb-girdle muscular dystrophy type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 147 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…The E3 ubiquitin ligase tripartite motif containing (Trim) 32 is a ubiquitously expressed multifunctional protein that plays a role in differentiation, tumor suppression, muscle physiology and regeneration [ 167 ]. Similar to MuRF1, it belongs to the TRIM family of proteins, which contain three zinc binding domains composed of a RING-finger, a coiled-coil region and a B-box type 1 and 2 [ 168 ].…”
Section: Protein Turnover In Muscle Is Regulated By a Precisely Acting Protein Degradation Pathwaymentioning
confidence: 99%
“…The E3 ubiquitin ligase tripartite motif containing (Trim) 32 is a ubiquitously expressed multifunctional protein that plays a role in differentiation, tumor suppression, muscle physiology and regeneration [ 167 ]. Similar to MuRF1, it belongs to the TRIM family of proteins, which contain three zinc binding domains composed of a RING-finger, a coiled-coil region and a B-box type 1 and 2 [ 168 ].…”
Section: Protein Turnover In Muscle Is Regulated By a Precisely Acting Protein Degradation Pathwaymentioning
confidence: 99%
“…This phenomenon could be explained by the functional role of TRIM32 as an E3 ligase, the residual of which resulted in increased proteasomal degradation in PDAC cells. 44,45 In summary, our study showed that ibr-7 alone or combined with gemcitabine exhibited potent anti-PDAC activity both in vitro and in vivo via the suppression of mTOR/p70S6K pathway, accompanied with significant downregulation of TRIM32. TRIM32 could form a positive feedback loop with mTOR/p70S6K, dictate malignant properties of PDAC cells and finally affected the drug sensitivity of gemcitabine.…”
Section: Trim32 Played a Key Role In The Progression Of Pdac Cellsmentioning
confidence: 69%
“…This phenomenon could be explained by the functional role of TRIM32 as an E3 ligase, the residual of which resulted in increased proteasomal degradation in PDAC cells. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Drosophila body wall skeletal muscles have emerged as an important model system to determine the mechanisms of muscle growth and differentiation [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Previously, we have found that FoxO overexpression in larval body wall skeletal muscles leads to myofiber atrophy and reduces developmental muscle growth [35], suggesting that the fruit fly Drosophila melanogaster can be used to identify evolutionary-conserved regulators of myofiber size [10,36,37].…”
Section: Introductionmentioning
confidence: 99%